2002
DOI: 10.1111/j.1745-3984.2002.tb01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Reliability of Ability‐Achievement Difference Scores: An Example Using the Kaufman Assessment Battery for Children

Abstract: In this study, we focused on increasing the reliability of ability‐achievement difference scores using the Kaufman Assessment Battery for Children (KABC) as an example. Ability‐achievement difference scores are often used as indicators of learning disabilities, but when they are derived from traditional equally weighted ability and achievement scores, they have suboptimal psychometric properties because of the high correlations between the scores. As an alternative to equally weighted difference scores, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(40 reference statements)
0
6
1
Order By: Relevance
“…This result may be specific to the present data or may indicate that RCA solutions are more sensitive than other methods to small perturbations in observed correlations. Findings also contradicted previous studies suggesting that RCA produces similar factors to other methods (Caruso & Cliff, 2000;Caruso & Witkiewitz, 2002); however this was only the case for the last factor extracted. For PCA and PAF solutions, the last factor was primarily made up of variables with low reliability (WCST-perseverative errors r xx 5 .64; WCST-categories r xx 5 .70), but for the RCA-varimax solution the composition of this factor emphasized more reliable variables (WAIS-III POI r xx 5 .93; Boston Naming Test r xx 5 .93).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…This result may be specific to the present data or may indicate that RCA solutions are more sensitive than other methods to small perturbations in observed correlations. Findings also contradicted previous studies suggesting that RCA produces similar factors to other methods (Caruso & Cliff, 2000;Caruso & Witkiewitz, 2002); however this was only the case for the last factor extracted. For PCA and PAF solutions, the last factor was primarily made up of variables with low reliability (WCST-perseverative errors r xx 5 .64; WCST-categories r xx 5 .70), but for the RCA-varimax solution the composition of this factor emphasized more reliable variables (WAIS-III POI r xx 5 .93; Boston Naming Test r xx 5 .93).…”
Section: Discussioncontrasting
confidence: 83%
“…These studies have found that RCA produces a similar factor 2 structure to other exploratory factor analytic techniques, but that RCA based composites yield more reliable cognitive difference scores than other techniques. Recent findings from a study by Caruso and Witkiewitz (2002) found that the principle method by which RCA generated reliable difference scores was through the creation of orthogonal composites using varimax rotation of factor weights. This suggests that the uncorrelated nature of factors derived using varimax rotation, regardless of the specific extraction, may be the primary driving force in the higher reliability of difference scores derived from factor analytic methods.…”
Section: Reliable Components Analysismentioning
confidence: 99%
“…where z r xx is the reliability of the intelligence test, r yy is the reliability of the reading test, and r xy is the correlation between the two tests (Caruso & Witkiewitz, 2002;Leeb & Weinberg, 1977;Overall & Woodward, 1975;Schulte & Borich, 1984). Using this formula, one would find that the higher the correlation between intelligence and reading tests, then the lower the reliability of the difference score (Caruso & Witkiewitz, 2002;Nunnally & Bernstein, 1994;Zimmerman, 1994).…”
Section: Measurement Errormentioning
confidence: 94%
“…Using this formula, one would find that the higher the correlation between intelligence and reading tests, then the lower the reliability of the difference score (Caruso & Witkiewitz, 2002;Nunnally & Bernstein, 1994;Zimmerman, 1994).…”
Section: Measurement Errormentioning
confidence: 97%
See 1 more Smart Citation